Legal Protection for Ownership of Land Rights in Housing Profit Sharing Agreements - Yunaitis, Yunaitis; Arlina, Sri (Jurnal Ius Constituendum, 2024)
This study aims to provide solutions and knowledge to legal protection, especially in ownership of land rights in performing housing benefit sharing agreements in Pekanbaru City, in addition, this study also aims to find out the application of such legal protection to land ownership rights by sharing the proceeds of such housing. It is expected that there will be no more intersections of legal certainty about housing sharing agreements among communitiesThe type of research used by the authors is the Normative Law method, As for the result of this study, the legal protection related to ownership of land rights in the housing sharing agreement specifically in the city of Pekanbaru can refer to Article 1338 paragraph (3) of the Civil Code, which says that the agreement must be executed in good faith, Where the deed of construction agreement containing the rights and obligations of the parties is a deed made in front of a notary that is authentic so that in the presence of such an agreement it becomes a law among them, whereas in its specific application in Kota Pekanbaru Land division cooperation is carried out according to the principle for units, the share of land owners in the form of ownership of house units with a certain percentage, as well as the developer also gets a share of the number of units according to the agreement. The size of each party's share depends on the price of the house unit. Where the higher the price of the house, the greater the share of the owner of the land, so that the parameters of its division correspond to the agreement promised in advance.